S and X band patch antenna for CubeSat nanosatellites - Meirambekuly, N.; Karibayev, B.A.; Temirbayev, A.A.; Imanbayeva, A.K. (Recent Contributions to Physics, 2021)
The CubeSat concept has become very popular with both university groups and researchers, space agencies, governments and companies. CubeSat offers a fast and affordable way for a wide range of stakeholders to be active in space. Due to the high degree of modularity and widespread use of off-the-shelf commercial subsystems, CubeSat projects can be prepared for flight much faster than using traditional satellite schedules usually within one to two years. In this paper, we have considered a model of an S and X band patch antenna for CubeSat nanosatellites in the field of Earth remote sensing (ERS). The antenna dimensions were determined and designed according to the dimensions of the small spacecraft. The shape of the emitting part was formed using a geometric fractal with an anisotropic structure. Using the CST Microwave Studio software package, the electrodynamic, frequency characteristics and directional properties of the antenna were determined. The results of computer simulations demonstrate that the developed antenna concept has a multi-band property and meets all the parameters that are necessary for receiving and transmitting data in the S and X bands. It was also found that the anisotropic fractal structure allows the antenna to have several operating frequencies.